Representing the business perspectives in software requirement - Che Pa, Noraini; Jusoh, Yusmadi Yah; Mohd Sani, Nor Fazlida (2012)
A software requirement is vital for software development and having a valid requirements document is very important to ensure that the software development process can be carried out effectively. Exploiting the business process is necessary to identify the business process definition and activities to gather the software requirements for software development activities. In future the organization may continuously adapt its business model using the software requirements. Therefore, it is important for the organization to obtain flexibility by considering the mission and strategies for innovation and competitiveness. This paper presents a framework to identify the software requirements, at the abstraction level, which specify the task of the stakeholders. The proposed framework representing the business perspective in software requirements and was implemented on a case study.